Tyrosinemia type II: Novel mutations in TAT in a boy with unusual presentation - Gokay, Songul; Kendirci, Mustafa; Ustkoyuncu, Pembe Soylu; Kardas, Fatih; Bayram, Ayse Kacar; Per, Huseyin; Poyrazoglu, Hatice Gamze (Wiley-Blackwell, 2016)
Tyrosinemia type II is a rare autosomal recessive disorder caused by deficiency of tyrosine aminotransferase (TAT). It may occur with ocular and cutaneous symptoms with or without mental retardation, but epileptic seizure is a rare presentation of this disease. Herein we report the clinical, biochemical and genetic features of a 4-year-old boy who presented with afebrile seizure and photophobia. Genomic DNA was obtained from peripheral blood leukocytes from the whole family. Sequencing analysis was performed using the MiSeq next-generation sequencing platform. Sequencing of TAT indicated two new homozygous mutations p.L312P (c.935T>C) and p.T408M (c.1223C>T) for the proband and his asymptomatic sister. During a 2 year follow-up period, the patient had overall poor compliance with protein-restricted diet, but his asymptomatic sister had good compliance with the diet. Cognitive function of the patient worsened steadily, but his asymptomatic sister maintained normal mental status. Tyrosinemia type II should be considered in the differential diagnosis of children presenting with epileptic seizure and photophobia; furthermore, early diagnosis and protein-restricted regimen are important to reduce the risk of long-term complications of tyrosinemia type II such as mental disability.
Keywords: cognitive function; epileptic seizure; low-protein diet; tyrosine aminotransferase; tyrosinemia type II